PMO-071 Eleven year regional UK cohort study reveals distinctly different temporal trends between neonatal and paediatric home enteral tube feeding. (28th May 2012) - Paxton, C E; Wade, K; Ardill, R; Lee, H; Eyles, L; Freer, Y; Menon, G; Wilson, D C
Abstract : Introduction: Home enteral tube feeding (HETF) is increasingly being used to provide nutrition support (NS) for children to promote growth and development. It is unclear if there are differences in the extent of use and temporal usage trends between neonatal and paediatric clinical practice. Aims: To determine: Absolute numbers of children and neonates discharged on HETF from the regional (SE Scotland) tertiary paediatric and neonatal units, the temporal trends in both paediatric and neonatal HETF over an extended period, and the comparison of these trends. The numbers of neonates transferred on enteral tube feeding (ETF) from the regional neonatal to the regional paediatric unit over the last 2 years of the time period and their outcome in terms of need for HETF. Methods: A retrospective cohort study (database and clinical note review) to compare numbers of children within the population of 838 573 in Lothian discharged on HETF from the single SE Scottish regional neonatal unit and the single SE Scottish regional paediatric unit, and their inter-relationships. All children and neonates discharged on HETF over the study period 1 July 2000–30 June 2011 were included. The fate of neonatal transfers requiring ETF to the paediatric centre was studied over the period of 1 July 2009–30 June 2011. Results: 485 Lothian children were discharged on HETF from the regional paediatric hospital (paediatric HETF) compared with 114 from the neonatal unit (neonatal HETF) over the same time period. Over the study period a rise in numbers requiring paediatric HETF was observed (average of 34 per year in 2000–2005 increasing to 55 per year in 2006–2011), however there was a decreasing number requiring neonatal HETF (average of 16 per year in 2000–2005 decreasing to 8 per year in 2006–2011). HETF was primarily used short term in the neonatal group for immaturity alone. During the 2-year period of the study 7/2009–6/2011, 20 neonates were transferred to the regional paediatric unit on ETF; 11 (55%) were subsequently discharged on HETF from the paediatric unit, but these neonatal transfers only accounted for 10% of the total of 103 paediatric HETF discharges. Conclusion: These novel data firstly demonstrate that the incidence of HETF usage on discharge from a UK paediatric regional centre continues to increase while that from the neonatal unit serving the same region is falling, and secondly that sick neonates transferred on ETF make up only a small number of incident paediatric HETF cases. Competing interests: None declared.